New Economic Sociology: Theoretical Achievements and Contemporary Challenges - Nonchev, Andrei (Research Papers, 2016)
This study presents some basic theoretical achievements and key concepts of the “new economic sociology”, which pretends to explore not peripheral economic phenomena, but fundamental economic processes. The theoretical programme of the new economic sociology is conceptualised in contrast with the assumptions of the neoclassical economics. The contributions of Bulgarian scholars to the analysis of important issues in the field of economic sociology are also highlighted. The study suggests hypotheses to explain the symptoms of recent slowdown in the development of economic sociology and possible perspectives for new theoretical breakthroughs. They are discussed in the context of contemporary societal challenges and conflicts, which seek their economic-sociological interpretation.
Keywords: New economic sociology; “embeddedness” of economic action; Economic institutions; Social construction of markets; Social capital; Social networks